Penilaian Dampak Lingkungan dan Upaya Pengelolaan Lingkungan Kegiatan Peternakan Unggas (Studi Kasus: Peternakan Unggas, Garut-Indonesia) - Munfarida, Ida (Al-Ard: Jurnal Teknik Lingkungan, 2022)
Poultry farm is one of the important sectors in meeting human needs for animal protein, but it was not correlated with the availability of poultry meats due to their limited production. In order to provide an adequate source of animal protein, especially in Garut Regency, the initiator plans to develop the poultry farm located in Sirnagalih Village, Garut Regency. It is necessary to build environmentally friendly poultry farms that implement sustainable development. This study analyzes the environmental impact of poultry farm in accordance with sustainable development. This study aims to analyze the environmental impact of “Sirnagalih Poultry Farm” in Garut Regency as an Environmentally Friendly Poultry Farm. The research was conducted by using quantitative and qualitative descriptive analysis. Quantitative analysis was used to analyse land use, water concumption, poulty manure and poultry carcass. The qualitative descriptive analysis explains the environmental management. Based on land use analysis, the BSC (Basic Structural Coefficient) is 65.92% consisting of poultry buildings, feed warehouses and supporting facilities. The GBC (Green Basic Coefficient) is 16.42%. Wastewater from poulty farm can be treated by a wastewater treatment plant. Animal manure waste can be managed by composting, while poultry carcass management and green open space can refer to Government Regulations.